Археологічні з’їзди та розвиток кримознавчих досліджень за дорадянської доби - Непомнящий, А.А. (Питання історії науки і техніки, 2007)
В статье проанализирована роль Археологических съездов, созываемых в Российской
империи, для развития историко-крымоведческих исследований. На основе просмотра
«Трудов» съездов автором выявлен корпус ранее неизвестных публикаций крупных ученых,
что дополняет наше представление об их творчестве. Приведена ранее неизвестная информация о попытке проведения подобного ученого форума в Крыму. A research by Prof. Andrej Nepomnyaschiy based on a very wide range of archive sources
recreates avidities in the field of the Crimean studies, preservation and restoration of the land’s
antiques. For the first time documents of tens of archives funds and various central, state, department
archives, manuscript departments, scientific libraries, funds and museum of Ukraine and the
Russian Federation come into use of scholars due to the author. «Province-centre» scientific links
formed in the Crimean studies are restored in the research. It shows the development of intellectual
landscape of the Crimean provinces.